The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1080/20004508.2019.1607708
|View full text |Cite
|
Sign up to set email alerts
|

Considering the past and present of Romani in Sweden: secondary school pupils’ thinking and caring about the history of the Romani in national tests

Abstract: In this study, we analyse 126 secondary pupils' responses to national test questions designed to make them think and care about the history of national minorities in Sweden. Using a mixed method approach we find that historical thinking and empathy as caring are tightly interlinked in the responses. In particular, the cognitive act of corroborating historical sources about the treatment of minorities is linked to historical empathy as caringwhile sourcing seems like a separate process. We also find that pupils… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…The test was called 'The Development Line of Intercultural Interaction', and it focused on the Roma peoples' situation in the past, present and future. The test was composed of a handful of multiple-choice questions and three essay questions, designed primarily to test and stimulate historical thinking and empathy skills (see Nolgård and Nygren, 2019 for an analysis). The test was taken by about 25 per cent of all Swedish Year 9 students (ages 15 and 16).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The test was called 'The Development Line of Intercultural Interaction', and it focused on the Roma peoples' situation in the past, present and future. The test was composed of a handful of multiple-choice questions and three essay questions, designed primarily to test and stimulate historical thinking and empathy skills (see Nolgård and Nygren, 2019 for an analysis). The test was taken by about 25 per cent of all Swedish Year 9 students (ages 15 and 16).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, history education researchers have debated what events to bring to the fore as historically significant in school history, and also what sets of criteria might be deployed by students to apply judgement about the significance of a historical event -that is, why, how and in what ways event(s) and human experiences of the past implicate the present and future (see Arthur and Phillips, 2000;Counsell, 2004Counsell, , 2011Davies, 2011). Although interesting, the question of historical significance and models for teaching and learning relating to historical explanation is beyond the scope of the present investigation, and thus this paper will not offer an in-depth analysis of students' use of second-order concepts (for such an analysis in the context of high-stakes history tests, see, for example, Samuelsson and Wendell, 2016;Nolgård and Nygren, 2019). Research on students' narrational practices of historical change has concluded that a basic understanding of chronology is key for students in order to fully grasp complex ideas of interdependent concepts such as continuity and change, cause and consequence, or progress and decline (see, for example, Levstik and Barton, 1996;Lévesque, 2008;Nersäter, 2014).…”
Section: The Complexity Of Teaching and Learning About Historical Change For Social Change In The Present And Futurementioning
confidence: 99%
See 1 more Smart Citation
“…In the domain of history research, a concept of historical empathy has been used to assess the cognitive aspect of perspective taking, or perspective recognition, but also the affective responses to the past, historical empathy as caring (Brooks, 2011;Nolgård & Nygren, 2019). Thus, the cognitive aspect of historical empathy is conceptually near moral perspective-taking, whereas historical empathy as caring -caring that people of the past were treated unjustly, or still are -can be seen as parallel to emotional empathy.…”
Section: Similarities Between Historical and Moral Consciousnessmentioning
confidence: 99%
“…A key aspect here has been to focus on the disciplinary aspects of history as a way of reaching a consensus between conflicting narratives. Sweden presents a different case where national history generally is regarded with consensus instead of being a source of dispute (e.g., Danielsson Malmros, 2012;Olofsson et al, 2017;Samuelsson, 2017;Zander, 2001), even though, of course, Swedish history does contain topics that are challenging and could be approached from conflicting perspectives (e.g., Alvén, 2017;Indzic Dujso, 2015;Linderborg, 2001;Lindmark & Sundström, 2017;Lozic, 2010;Nolgård & Nygren, 2019;Runcis, 1998). While we have knowledge and an academic discussion of how conflict-ridden societies approach their national history in history education, we know less about how national history is approached in societies with a low degree of conflict regarding its national past and what challenges, if any, that may pose to history education.…”
Section: Introductionmentioning
confidence: 99%